Monitoria comunitária independente ao PASD-PE COVID-19. Segunda Fase - Maputo e Namaacha - Plataforma da Sociedade Civil Moçambicana para a Protecção Social (PSC-PS) (Plataforma da Sociedade Civil Moçambicana para a Protecção Social (PSC-PS), 2021)
Os principais resultados da monitoria realizada em Montepuez destacaram a necessidade de: • Fortalecimento de mecanismos comunitários de participação e reforço do diálogo social entre comunidades e governo local; • Maior apropriação dos programas de protecção social básica por parte das comunidades e a necessidade de atribuir mais voz e protagonismo dos beneficiários sobre os serviços sociais prestados a nível destes programas; • Melhor comunicação e disseminação de informação estratégica sobre os programas de protecção social junto às comunidades, incluindo mais clareza sobre critérios de elegibilidade, valor dos benefícios, periodicidade e duração; • Maior mobilização social com vista a promover comunidades mais informadas e capacitadas para reivindicar os seus direitos sociais básicos; • Reforço de mecanismos de reclamações e queixas (clareza sobre como acessá-los); • Maior apoio para facilitação do acesso dos beneficiários aos pagamentos, em particular aqueles que precisam de auxílio para utilização dos telefones a partir dos quais recebem seus benefícios; • Ampliação dos métodos de pagamento para facilitar o acesso dos beneficiários às transferências.
Keywords: G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; health - COVID-19 / saúde – COVID-19; social protection / proteção social

Actualidade Económica de Moçambique: Preparação para Recuperação (World Bank Group, 2021)
The global pandemic has taken a heavy toll on Mozambique’s economy. In 2020, the country experienced its first economic contraction in nearly three decades. COVID-19 (coronavirus) hit the economy as it was attempting to recover from the slowdown triggered by the hidden debt crisis and the tropical cyclones in 2019. Real gross domestic product (GDP) contracted by 1.3 percent in 2020, compared to a pre-Covid estimate of 4.3 percent, as external demand declined, domestic lockdown measures disrupted supply chains and depressed domestic demand, and liquified natural gas (LNG) investments were delayed. COVID-19 has caused a sudden income loss for enterprises and households, worsening living conditions, especially for the urban poor largely engaged in the informal sector. According to the National Institute of Statistics, as of June 2020, about 120,000 jobs were lost and 63,000 employment contracts suspended, with women being the most affected. Around 3 percent of the firms affected were forced to cease their activity. Services activities are the hardest hit. The tourism and hospitality industries have particularly suffered a steep decline in revenues. COVID-19 has jeopardized years of hard-won development gains, with about one million people estimated to have slipped into poverty in 2020 (as measured by the international poverty line of 1.90 US Dollars per day). While there is great uncertainty about the path of the pandemic, the economy is expected to gradually recover from 2021 as aggregate demand rebounds and LNG investments and extractive production gain momentum. Despite the expected recovery, the widespread deployment of COVID-19 vaccines will be at the core of a resilient recovery. This Economic Update explores the implications of COVID-19 for the economy, businesses and households. It makes recommendations for moving forward—in the short-term relief phase, as well as over the medium and longer term in order to 'build back better~^!!^.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; development partners / parceiros de cooperação; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19; health / saúde; private sector / setor privado

Mozambique Economic Update : Setting the Stage for Recovery (World Bank Group, 2021)
The global pandemic has taken a heavy toll on Mozambique’s economy. In 2020, the country experienced its first economic contraction in nearly three decades. COVID-19 (coronavirus) hit the economy as it was attempting to recover from the slowdown triggered by the hidden debt crisis and the tropical cyclones in 2019. Real gross domestic product (GDP) contracted by 1.3 percent in 2020, compared to a pre-Covid estimate of 4.3 percent, as external demand declined, domestic lockdown measures disrupted supply chains and depressed domestic demand, and liquified natural gas (LNG) investments were delayed. COVID-19 has caused a sudden income loss for enterprises and households, worsening living conditions, especially for the urban poor largely engaged in the informal sector. According to the National Institute of Statistics, as of June 2020, about 120,000 jobs were lost and 63,000 employment contracts suspended, with women being the most affected. Around 3 percent of the firms affected were forced to cease their activity. Services activities are the hardest hit. The tourism and hospitality industries have particularly suffered a steep decline in revenues. COVID-19 has jeopardized years of hard-won development gains, with about one million people estimated to have slipped into poverty in 2020 (as measured by the international poverty line of 1.90 US Dollars per day). While there is great uncertainty about the path of the pandemic, the economy is expected to gradually recover from 2021 as aggregate demand rebounds and LNG investments and extractive production gain momentum. Despite the expected recovery, the widespread deployment of COVID-19 vaccines will be at the core of a resilient recovery. This Economic Update explores the implications of COVID-19 for the economy, businesses and households. It makes recommendations for moving forward—in the short-term relief phase, as well as over the medium and longer term in order to 'build back better~^!!^.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19; health / saúde; private sector / setor privado

Relatório de Pesquisa Desigualdades e Resistência em Tempos de Pandemia: Impactos Da COVID-19 Nas Mulheres do Mercado Informal - Osório, Conceição; Loforte, Ana Maria; Vilanculo, Sérgio (WLSA Moçambique, 2021)
Este relatório de pesquisa buscou especificamente identificar no contexto mundial, regional e nacional as estratégias e as políticas públicas relativamente à situação das raparigas e mulheres, analisar as narrativas e discursos das organizações da sociedade civil e instituições de pesquisa, tanto as que têm como foco os direitos humanos, como as que definem como objecto a promoção da igualdade de género, e analisar o conteúdo dos media nacionais sobre a Covid-19, com destaque para as representações sobre violência de género. Para a realização da pesquisa foi importante a definição do grupo alvo, as mulheres que trabalham no informal, por serem das mais afectadas pela situação criada pela Covid-19, sendo muito pouco conhecidas as suas vozes, os seus problemas, necessidades e expectativas. A pesquisa foi enquadrada no Projecto “Mulheres e direitos humanos no contexto da COVID-19 em Moçambique” e surgiu no âmbito de uma parceria entre a WLSA Moçambique com as Aliadas e o CESC, procurando conhecer melhor como é que, em situação de pandemia, se configuravam os direitos humanos das mulheres, considerando as desigualdades estruturais e as relações desiguais de poder.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; civil society / sociedade civil; gender / género; health - COVID-19 / saúde – COVID-19; health / saúde; informality / informalidade

Navigating Civic Space in a Time of COVID-19: The Case of Mozambique - Pereira, Crescêncio; Forquilha, Salvador; Shankland, Alex (Institute for Social and Economic Studies, 2021)
This report builds on the Action for Empowerment and Accountability (A4EA) research project Navigating Civic Space, which seeks to analyze the extent to which COVID-19 is contributing to the opening or closing of space for civic action in three countries, namely Mozambique, Nigeria and Pakistan. Focusing on Mozambique, the report uses theoretical and methodological tools produced by the work stream and is essentially structured around the three main research questions: What is known about the civic space trend in Mozambique before the arrival of the COVID-19 pandemic?; How are different actors responding to the COVID-19 pandemic affecting the civic space in Mozambique?; What are the medium and long term implications for governance in Mozambique?
Keywords: G - Mozambique / Moçambique; L - english / inglês; civic space / espaço cívico; health - COVID-19 / saúde – COVID-19

African Economic Outlook 2021: From Debt Resolution to Growth: The Road Ahead for Africa - African Development Bank (African Development Bank, 2021)
The 2021 edition of the African Economic Outlook focuses on debt resolution, governance, and growth in Africa. Chapter 1 examines Africa’s growth performance and outlook amid the COVID–19 pandemic. The chapter emphasizes policy options to mitigate the effects of the pandemic in the short, medium, and long terms. Chapter 2 explores the causes and consequences of Africa’s debt dynamics by showing how the changing structure and composition of debt create vulnerabilities. In chapter 3, the report takes stock of the challenges in the current global architecture for debt resolution and explores the link between governance and growth with an emphasis on proposed reforms to improve the processes of debt resolution, governance, and sustainable growth
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; governance / governação; health - COVID-19 / saúde – COVID-19

Unpacking the Potential Socioeconomic Impact of the Coronavirus Pandemic in Mozambique: A United Nations Situation Analysis and Policy Recommendations - United Nations Mozambique (United Nations, 2020)
The Coronavirus pandemic arrives in Mozambique at a time when, after several years of modest economic performance, the Mozambican economy was starting to show signs of recovery. Hence, the latest projections of the IMF of November 2019 had the Mozambican economy growing at 6% in 2020, with medium term projections reaching 9% and above after 2023, following the initiation of LNG exploration operations in the north of the country. Despite this improving macroeconomic outlook prior to the outbreak of the Coronavirus pandemic, living conditions for many Mozambicans remain harsh. Poverty afflicts almost half of the population, 46.1% according to the 2014/15 national household survey, and many people continue without access to basic services, with the proportion of Mozambicans with access to basic water supply, basic sanitation and electricity remaining at very low levels: 55.7%, 29.4% and 27.4% in 2017, respectively. Moreover, despite improvements in healthcare conditions, Mozambicans, especially women and children, continue to be severely afflicted by disease and sickness. In general, living conditions tend to be worse in rural than in urban parts of the country. The coronavirus pandemic is almost certainly going to change this short- and medium-term economic outlook and could potentially have a very significant socioeconomic impact in Mozambique. However, while all available evidence points in this direction, at this stage it is difficult to ascertain and quantify the extent of this impact, given the speed at which things are changing around the world and the uncertainly surrounding the epidemiological profile of the Coronavirus, which makes it hard to assess how long the containment and lockdown measures being applied around the world will need to remain in place. While a detailed quantification of the socioeconomic impact of the coronavirus pandemic may not be feasible, it is still useful to identify possible transmission channels through which the pandemic may affect the Mozambican economy and society. It is also useful to identify key issues that are likely shape shortand medium-term socioeconomic prospects in Mozambique as a result of the Coronavirus pandemic outbreak in Mozambique. The following sections outline some of these.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19; health / saúde

Democracy Index 2020 In sickness and in health? - The Economist Intelligence Unit (The Economist, 2020)
The main focus of the report is the impact of the coronavirus (Covid-19) pandemic on democracy and freedom around the world. It looks at how the pandemic resulted in the withdrawal of civil liberties on a massive scale and fuelled an existing trend of intolerance and censorship of dissenting opinion (see page 14). The report also examines the state of US democracy after a tumultuous year dominated by the coronavirus pandemic, the Black Lives Matter movement and a hotly contested presidential election (see page 42). The results by region are analysed in greater detail in the section entitled “Democracy around the regions in 2020” (see page 26).
Keywords: *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; civil society / sociedade civil; health - COVID-19 / saúde – COVID-19

Mozambique Annual Report 2020: Responding to a Year of Crisis - Wojnar, Andrea M; Lomelin, Jessica; Baker, Daniel; Salu, Karlina; Macangira, Assane; Manjate, Epidauro (UNFPA, 2020)
In the case of Mozambique, the pandemic came on the heels of two destructive cyclones that had devastated large parts of the country in 2019 and whose consequences were still being felt. In northern Mozambique, increasing violence in Cabo Delgado province resulted in a surge of internally displaced persons into local communities in Cabo Delgado, Nampula and Niassa provinces. With host communities ill equipped to meet the needs of those displaced, this population movement created a new humanitarian crisis in the midst of the pandemic. Like all of our governmental, civil society and donor partners, the resilience of UNFPA was tested, and we had to adjust quickly after the first case of COVID-19 was confirmed in March and the Government declared a state of emergency. At the most basic level, women continued to get pregnant and babies were still being born, even in the middle of a pandemic. Addressing the needs of adolescent girls and young women could not be put on hold. Helping to meet the needs of the symbolic target of UNFPA’s work – “the 10-year-old girl” – could not wait until she was 11. Helping to meet her aspirations for the future, advocating and working for her growth and self-fulfillment as a woman leading a healthy, productive and violence-free life – these could not wait a year.
Keywords: G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - COVID-19 / saúde – COVID-19; health / saúde; youth / juventude

Flash Appeal for COVID-19 - Mozambique (United Nationals Office for the Coordination of Humanitarian Affairs (OCHA))
Provides an overview of the COVID-19 situation in Mozambique, details response strategy, coordination, capacity, and constraints. Then goes on to review sectoral impacts, including in internally displaced peoples, education, food security & livelihood, health, nutrition, protection, WASH, and shelter.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; health - COVID-19 / saúde – COVID-19; health / saúde